2016
DOI: 10.4049/jimmunol.1501659
|View full text |Cite
|
Sign up to set email alerts
|

Anti-C1q Autoantibodies from Systemic Lupus Erythematosus Patients Induce a Proinflammatory Phenotype in Macrophages

Abstract: Anti-C1q autoantibodies (anti-C1q) are frequently found in patients with systemic lupus erythematosus (SLE) and correlate with the occurrence of proliferative lupus nephritis. A previous study of anti-C1q in experimental lupus nephritis demonstrated an important role for FcγRs in the pathogenesis of lupus nephritis, suggesting a direct effect on phagocytes. Therefore, we developed an in vitro model to study the effect of SLE patient–derived anti-C1q bound to immobilized C1q (imC1q) on human monocyte-derived ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
3
20
0
Order By: Relevance
“…In this context, C1q has been shown to elicit upregulated expression of MerTK receptor, which is involved in the process of dead cell removal, termed efferocytosis (33). Moreover, it has been described that stimulation of macrophages with C1q leads to a polarization of these cells toward an anti-inflammatory state (34). Therefore, we aimed to investigate the phenotype of HMDMs in our in vitro model.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, C1q has been shown to elicit upregulated expression of MerTK receptor, which is involved in the process of dead cell removal, termed efferocytosis (33). Moreover, it has been described that stimulation of macrophages with C1q leads to a polarization of these cells toward an anti-inflammatory state (34). Therefore, we aimed to investigate the phenotype of HMDMs in our in vitro model.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that opsonization of IgG from lupus promoted rapid clearance of early apoptotic cells, but it changed early apoptotic cells from anti-inflammatory to proinflammatory properties, which indicated a contributor in the pathogenesis of lupus. Sophia et al demonstrated that anti-C1q from lupus induced a proinflammatory phenotype in macrophages reversing the effects of C1q alone [26]. In a recent research, the Ro 60 autoantigen could bind endogenous retroelements and regulate inflammatory gene expression [27], which might provide a direction to investigate the underling mechanisms of proinflammatory property of patient IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines, such as TNF-α, IL-1, and IL-6, play pivotal roles in inflammation and the maturation of B cells, and have been proven to be closely related to the pathophysiology of SLE [25,26]. IL-6 is produced by TNF-α and supposedly upregulates the number of inflammatory cells [27].…”
Section: Discussionmentioning
confidence: 99%